LUTO NA ESCOLA: UM CUIDADO NECESSÁRIO - Marques, Patrícia Regina Moreira (2012)
The present work deals with an investigation about the presence and the process of mourning for death in schools and also how teachers, coordinators and principals can support bereaved students. A significant rate of student deaths demonstrates that the process experienced by bereaved students is reality present in schools. For its relevance, it is understood to be essential that the issue be considered in school education. The methodology option for the development of the study was guided by conducting a literature review, in order to theoretically outline a historical and social perspective established mainly for Paiva (2011), Kovács (2003), Franco (2002), Kübler-Ross (1996). It was decided, also, to make use of news and documentaries. To perform the empirical research, the investigation was focused in two public schools at Greater Sao Paulo and 23 subjects including teachers, principals and coordinators. In this series, 13 subjects were from school A and 10 from school B, and all of them work directly with the students. In a first step, a structured questionnaire was applied and answered initially by 23 subjects. In the second stage of the research, it was used the depth interview as a method with a sample of 10 professionals (two principals, one coordinator and seven teachers). After answering the questionnaire, these professionals wished to participate voluntarily of the second step, in order to get further deepening about of issues related to the research in school. As references for data analysis, Queiroz (2003) and Demartini (2001) were chosen. The research allowed determining the presence and the process of mourning and death in schools and how teachers, coordinators and principals address the topic of the death, the mourning and the loss. The survey also sought to understand and ponder on the meanings that the educators have about death and mourning in the school context. This knowledge allowed to know how some teachers and other education professionals work (or not) with the grieving process in school. The analyses obtained from the themes revealed that some professionals who experience or experienced the pain of bereavement have difficulties in dealing with the theme at school because they not know how to handle this situation. Another considered issue is the lack of support from the school and the lack of staff training to deal with bereavement in school. The reports have shown the death of young people as a present reality in schools and occupying more and more space. This challenging issue does not end. There are many actions that schools need to make happen. This work proposes directions to further investigations and challenges.